Human rights in turmoil : facing threats, consolidating achievements - Lagoutte, Stéphanie (International studies in human rights, 2007)
Are human rights gaining or losing ground? This book contains essays by leading scholars and practitioners in the field of human rights, which explores the ways in which human rights are being challenged and weakened, but also strengthened in important and groundbreaking ways in different areas and settings.